Association of Discharge Aspirin Dose With Outcomes After Acute Myocardial Infarction. Issue 3 (21st July 2015) - Xian, Ying; Wang, Tracy Y.; McCoy, Lisa A.; Effron, Mark B.; Henry, Timothy D.; Bach, Richard G.; Zettler, Marjorie E.; Baker, Brian A.; Fonarow, Gregg C.; Peterson, Eric D.
<x xml:space="preserve">Abstract</x> Background— Aspirin is the most widely used antiplatelet drug postmyocardial infarction, yet its optimal maintenance dose after percutaneous coronary intervention with stenting remains uncertain. Methods and Results— We compared outcomes of 10 213 patients with myocardial infarction who underwent percutaneous coronary intervention and were discharged on dual-antiplatelet therapy at 228 US hospitals in the Treatment with ADP Receptor Inhibitors: Longitudinal Assessment of Treatment Patterns and Events after Acute Coronary Syndrome (TRANSLATE-ACS) study from 2010 to 2012. Major adverse cardiovascular events and bleeding within 6 months postdischarge were compared between high-dose (325 mg) and low-dose aspirin (81 mg) by using regression models with inverse probability-weighted propensity adjustment. Overall, 6387 patients (63%) received high-dose aspirin at discharge. Major adverse cardiovascular events risk was not significantly different between groups (high versus low: unadjusted 8.2% versus 9.2%; adjusted hazard ratio, 0.99; 95% confidence interval, 0.85–1.17). High-dose aspirin use was associated with greater risk of any Bleeding Academic Research Consortium–defined bleeding events (unadjusted 24.2% versus 22.7%; adjusted odds ratio, 1.19; 95% confidence interval, 1.06–1.33), driven mostly by minor Bleeding Academic Research Consortium type 1 or 2 bleeding events not requiring hospitalization (unadjusted 21.4% versus 19.5%; adjusted odds ratio, 1.19; 95% confidence interval, 1.05–1.34). Bleeding events requiring hospitalization were similar by aspirin dosing groups (unadjusted 2.8% versus 3.2%, adjusted odds ratio, 1.22; 95% confidence interval, 0.87–1.70). Similar associations were observed in landmark analyses accounting for aspirin dosing change over time, and across subgroup analyses by age, sex, baseline aspirin use, and type of ADP receptor inhibitor (clopidogrel versus prasugrel/ticagrelor). Conclusions— Among percutaneous coronary intervention–treated patients with myocardial infarction, high-maintenance-dose aspirin was associated with similar rates of major adverse cardiovascular events, but a greater risk of minor bleeding than those discharged on low-dose aspirin.